Reading culture development among the youth as a humanitarian-pedagogical problem - O. I. Kolesnikova; E. V. Russkhikh (Библиосфера, 2016)
The article deals with the problem of reading in a modern society, suggests ways of its solution evidently for the youth reading audience. The concept of an art-linguistic competence as a component of reading culture is substantiated. The esthetic potential of a literary text for the youth is considered as a mean of developing such competence. The authors propose the problem specific solutions in a process of the research program realization.